Oxo-amphiboles in mantle xenoliths: evidence for H2O-rich melt interacting with the lithospheric mantle of Harrow Peaks (Northern Victoria Land, Antarctica) - Gentili, S; Bonadiman, C.; Comodi, P.; Coltorti, M.; Zucchini, A.; Ottolini, L.; BIAGIONI, CRISTIAN (Mineralogy and Petrology, 2015)
Amphiboles are the most widespread hydrous metasomatic phases in spinel-bearing mantle peridotites from Harrow Peaks (HP), Northern Victoria Land (Antarctica). They occur both in veinlets and disseminated in the peridotite matrix (preferentially associated with clinopyroxene and spinel grains). Four amphibole crystals were investigated by single-crystal X-ray diffraction (SC-XRD), electron microprobe analysis (EMPA), secondary ion mass spectrometry (SIMS) and micro-Mössbauer spectroscopy; these crystal-chemical data allow to constrain upper mantle conditions during growth of these amphiboles and the role of volatile circulation during metasomatic processes in the Antarctic region. The HP amphiboles have low Mg# values (69.3–84.1), high TiO2 (2.74–5.30 wt%) and FeOtot contents (3.40 to 6.90 wt%). The Fe3+/Fetot ratios are significantly high (0.53–0.66). The W-site is mainly occupied by O2- (0.984–1.187 apfu) plus OH (H2O: 0.70–1.01 wt%) and minor F (0.04–0.24 wt%) and Cl (0.03–0.08 wt%). Consequently, HP amphiboles are actually characterized by a significant oxo component. The aH2O values were calculated at 1.5 GPa by dehydration equilibrium equations written as H2O-buffering equilibria among end-member components of amphibole and coexisting peridotite phases. Three out of four HP amphibole-bearing peridotites have values of aH2O ranging from 0.122 to 0.335; whereas one sample has aH2O remarkably higher (0.782) approaching an ideal H2O basalt solubility. The HP fO2 values, determined by the olivine-spinel-orthopyroxene oxygeobarometer (ΔQFM = −1.77 : +0.01), are remarkably different from those calculated on the basis of the amphibole dehydration equilibrium and the application of the dissociation reaction (ΔQFM = −2.60 : +6.8). The high aH2O and the extremely high fO2 values, determined by the oxy-amphibole equilibrium with respect to the redox conditions recorded by the co-existing anhydrous minerals (close to QFM buffer), revealed that: i) the amphibole-forming reaction is a relatively recent process with the ...